2002
DOI: 10.1523/jneurosci.22-21-09143.2002
|View full text |Cite
|
Sign up to set email alerts
|

DrosophilaHB9Is Expressed in a Subset of Motoneurons and Interneurons, Where It Regulates Gene Expression and Axon Pathfinding

Abstract: Motoneurons are an essential component of all metazoan nervous systems, but it is unknown whether there is an evolutionarily conserved mechanism for generating motoneurons during neurogenesis. In the vertebrate CNS, HB9/MNR2 transcription factors are specifically expressed in all somatic motoneurons and are necessary to distinguish motoneurons from interneurons, in part by repressing interneuron-specific gene expression. Here, we identify and characterize the single Drosophila ortholog of the HB9/MNR2 gene fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 23 publications
3
79
0
Order By: Relevance
“…To identify distinct neural subtypes, we generated single-marker atlases for additional transcription factor (TF) patterns: phospho-Mothers against Dpp ( pMad; all MNs), Bar (subset MNs), Dimmed (Dimm; most neurosecretory cells), Reversed polarity (Repo; glia), Apterous (Ap; subset interneurons, subset neurosecretory cells), Engrailed (En; subset interneurons, subset glia) and Hb9 (Exex -FlyBase; subset interneurons, subset MNs) ( Fig. 2A-G; supplementary material Data File S3) (Benveniste et al, 1998;Bourgouin et al, 1992;Broihier and Skeath, 2002;Garces et al, 2006;Layden et al, 2006;Lundgren et al, 1995;Mccabe et al, 2003;O'Connor, 2005;Odden et al, 2002;Park et al, 2004Park et al, , 2008Patel et al, 1989;Xiong et al, 1994). Notably, we built our atlas at a time point slightly before a subset of neuropeptide (Dimm+) neurons would begin to project out of the ventral nerve cord (VNC; Allan et al, 2003;Miguel-Aliaga, 2004), thus rendering our Dimm + neurons pMad-.…”
Section: Generation and Characterization Of The Atlas-builder Softwarementioning
confidence: 99%
See 1 more Smart Citation
“…To identify distinct neural subtypes, we generated single-marker atlases for additional transcription factor (TF) patterns: phospho-Mothers against Dpp ( pMad; all MNs), Bar (subset MNs), Dimmed (Dimm; most neurosecretory cells), Reversed polarity (Repo; glia), Apterous (Ap; subset interneurons, subset neurosecretory cells), Engrailed (En; subset interneurons, subset glia) and Hb9 (Exex -FlyBase; subset interneurons, subset MNs) ( Fig. 2A-G; supplementary material Data File S3) (Benveniste et al, 1998;Bourgouin et al, 1992;Broihier and Skeath, 2002;Garces et al, 2006;Layden et al, 2006;Lundgren et al, 1995;Mccabe et al, 2003;O'Connor, 2005;Odden et al, 2002;Park et al, 2004Park et al, , 2008Patel et al, 1989;Xiong et al, 1994). Notably, we built our atlas at a time point slightly before a subset of neuropeptide (Dimm+) neurons would begin to project out of the ventral nerve cord (VNC; Allan et al, 2003;Miguel-Aliaga, 2004), thus rendering our Dimm + neurons pMad-.…”
Section: Generation and Characterization Of The Atlas-builder Softwarementioning
confidence: 99%
“…Primary antibodies were mouse Eve 2B8 (1:50), mouse En 4D9 (1:10), and rat Elav (1:10), all from the Developmental Studies Hybridoma Bank (DSHB) developed under the National Institute of Child Health and Human Development (NICHD) and maintained by the University of Iowa; guinea pig Dimm (1:100; a gift from S. Thor, Linkoping University, Sweden); rat Repo (Campbell et al, 1994) (1:1000); rabbit pMad (pS1 1:300; Peter Ten Dijke, Leiden University Medical Center, Leiden, The Netherlands); chicken GFP (1:1000; Aves, Tigard, OR); rabbit Hb9 (Odden et al, 2002) (1:1000); and guinea pig Fox (Nechipurenko and Broihier, 2012) (1:20). Secondary antibodies were from Invitrogen/Molecular Probes and were used according to the manufacturer's instructions.…”
Section: Embryo Immunostaining and Stagingmentioning
confidence: 99%
“…The homeodomain protein Hb9 is an evolutionarily conserved transcription factor, expressed in somatic motoneurones and interneurones of Drosophila (Odden et al, 2002), in postmitotic chick motoneurones (Tanabe et al, 1998) and in mouse progenitor and postmitotic neurones (Arber et al, 1999). By using transgenic technology in mice, GFP expression can be driven by a promoter for the Hb9 gene and subsequently neurones that express Hb9 will, for the most part, express GFP (Wichterle et al, 2002).…”
Section: Genetic Techniques For the Identification Of Mammalian Spinamentioning
confidence: 99%
“…Interestingly, it has been observed that motoneurons may still form in isolated A4.1 explants (Okada et al, 1997). We used two motoneuron markers, Ci-ChAT, which encodes cholinergic acetyltransferase (Takamura et al, 2002;Yoshida et al, 2004), and the Ciona homologue of HB9 and MNR2 genes, which play a crucial role in motoneuron specification in other systems, and of which there is one representative in the Ciona genome, Ci-HB9/MNX (Broihier and Skeath, 2002;Odden et al, 2002;Shirasaki and Pfaff, 2002;Wada et al, 2003). Expression of these motoneuron markers was completely dependent on an intact Nodal signalling pathway ( Fig.…”
Section: A Collection Of Neural Plate Markers To Investigate Neural Pmentioning
confidence: 99%